PDF Mapping Consumer Awareness of Halal Food Across Countries: A Python-Based Google Trends Study: Pemetaan Minat Konsumen terhadap Makanan Halal di Berbagai Negara: Studi Google Trends Berbasis Python - Koswara, Asep (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2025)
This study aims to map global consumer awareness of halal food through the analysis of search trends using the keyword “halal food” on Google Trends from July 2020 to July 2025. Employing a Python-based data collection and visualization method, this research explores the intensity, geographic distribution, related rising queries, and seasonal patterns of online interest. The findings show that awareness is highest in Southeast Asian countries, particularly Singapore, Brunei, and Malaysia, while Western countries like the United Kingdom, Canada, and Australia demonstrate growing interest. Related search terms highlight the rise of halal-branded fast food and localized food festivals, suggesting a shift in consumer engagement. Seasonal trends correlate strongly with Islamic religious events such as Ramadan and Eid. The study offers a novel perspective by integrating behavioral data and digital tools to uncover dynamic awareness patterns, contributing to the halal consumer behavior literature. The implications suggest new marketing strategies for halal food providers, especially in emerging multicultural markets, by aligning offerings with search behavior and cultural timing.